2020
DOI: 10.1111/ele.13649
|View full text |Cite
|
Sign up to set email alerts
|

Residence time determines invasiveness and performance of garlic mustard (Alliaria petiolata) in North America

Abstract: While biological invasions have the potential for large negative impacts on local communities and ecological interactions, increasing evidence suggests that species once considered major problems can decline over time. Declines often appear driven by natural enemies, diseases or evolutionary adaptations that selectively reduce populations of naturalised species and their impacts. Using permanent long‐term monitoring locations, we document declines of Alliaria petiolata (garlic mustard) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Additional studies suggest there may be a drop in garlic mustard densities over time as well (Blossey et al 2020). However, our sites were located in forests with similar land use histories and forest age and were locally proximate to one another with likely similar invasion history, while studies on declines in age and density have been conducted at the regional-to-continental scale (Blossey et al 2020;Winterer et al 2005). Additionally, research with garlic mustard has demonstrated that populations in the invaded range experience less herbivory, but do not decrease defensive chemical production compared to plants in the home range (Lewis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies suggest there may be a drop in garlic mustard densities over time as well (Blossey et al 2020). However, our sites were located in forests with similar land use histories and forest age and were locally proximate to one another with likely similar invasion history, while studies on declines in age and density have been conducted at the regional-to-continental scale (Blossey et al 2020;Winterer et al 2005). Additionally, research with garlic mustard has demonstrated that populations in the invaded range experience less herbivory, but do not decrease defensive chemical production compared to plants in the home range (Lewis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, data from long-term monitoring of populations of garlic mustard in the invaded range suggests that glucosinolate concentration declines in garlic mustard populations over time (Lankau et al 2009). Additional studies suggest there may be a drop in garlic mustard densities over time as well (Blossey et al 2020). However, our sites were located in forests with similar land use histories and forest age and were locally proximate to one another with likely similar invasion history, while studies on declines in age and density have been conducted at the regional-to-continental scale (Blossey et al 2020;Winterer et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies either showed no impact of garlic mustard on soil biota or a weak effect with other stronger ecosystem drivers (Burke 2008 , Barto et al 2010 , Koch et al 2011 , Phillips-Mao 2012 ). Confounding variables influencing the impact of garlic mustard on the soil biota include the presence of white-tailed deer (Odocoileus virginianus; Burke et al 2019 ), concentration of soil nutrients, particularly nitrogen (Castellano and Gorchov 2012 , Poon and Maherali 2015 , Anthony et al 2020 , Cope et al 2021 ), and time since invasion (Barto et al, 2010 , 2011 , Lankau, 2010 , 2011b , Davis et al, 2012 , 2014 , 2015 , Blossey et al 2021 ).…”
Section: Mechanisms For Garlic Mustard Invasion Success Across Ecolog...mentioning
confidence: 99%
“…Only 2 of the 12 regional (more than three state) studies since 2008 incorporated data collected over a decadal time scale (Averill et al 2018 , Blossey et al 2021 ), with 2 others using herbarium specimens to estimate invasion processes over regional scales over up to two centuries (Lankau et al 2009 , Clark et al 2018 ). Bialic-Murphy and colleagues ( 2020 ) used 6 years of detailed demographic data at a single site to find that garlic mustard's impact differed greatly over time and other studies have found dramatic decreases (Lankau 2012b , Murphy and McCarthy 2014 , Nuzzo et al 2017 , Faison et al 2019 , Anderson et al 2021 , Blossey et al 2021 ) or increases (Rooney and Rogers 2011 ) in garlic mustard abundance over years to decades. These findings indicate that annual and short-term studies are poor representatives of future dynamics and point to the strong need for longitudinal studies of garlic mustard invasion (Lankau et al 2009 , Blossey et al 2021 ).…”
Section: How and Where Has Garlic Mustard Been Studied?mentioning
confidence: 99%
See 1 more Smart Citation